Relationship between Stress Level and Sleep Quality of New Santri in Dormitory X of Darul 'Ulum Islamic Boarding School Jombang - Fadilah, Nurul; Widiatie, Wiwik; Mukarromah, Indah (Promotion and Prevention in Mental Health Journal, 2023)
The stress they feel hurts sleep patterns, and difficulty sleeping soundly can affect sleep quality. Other impacts are emotional changes (feeling easily tired and having difficulty relaxing.) and behavioral changes (lazy learning, breaking rules, and running away from pesantren). The study aimed to analyze the relationship between stress levels and sleep quality of new students in Dormitory X of Darul 'Ulum Jombang boarding school. A retrospective analytic research design, a sample of 59 respondents, was used using a random sampling technique. This study used PSS and PSQI questionnaires; statistical tests used Spearman rho with a significance of α ≤ 0.05. As a result, 59.3% have a moderate level of stress with poor sleep quality; Pvalue < α (0.003 < 0.05) means that there is a relationship between stress levels and the quality of sleep of new students in dormitory X Ponpes Darul 'Ulum Jombang. The correlation coefficient value of 0.378 shows a weak positive correlation. Thus, the significant relationship between stress levels and sleep quality is not very strong. This study shows that in the age group 13-16 years, almost half (81.4%) have been able to manage stress, have a high school education level, almost half 54.2% know how to manage stress, have a comfortable environment, almost half (66.1%), get social support from friends almost half (72.9%), have a target to be achieved (71.2%) so that it can reduce stress levels and poor sleep quality to improve. It is important to understand how to balance students' obligations and sleep quality, as well as how to provide nursing interventions to improve sleep quality and reduce stress levels in students with other stress management measures.